Managing product variety in quotation processes - Bramham, Jo; MacCarthy, Bart L.; Guinery, Jane (Emerald, 2005)
Purpose – Manufacturers across many sectors increasingly operate in high variety environments. Research evidence suggests that variety has a negative impact on performance. However, the research literature is limited on the enablers that allow variety to be managed effectively and efficiently at the “front-end” of an organisation and in quotation processes in particular. Design/methodology/approach – This paper presents case analysis of the quotation processes from manufacturers operating in high-variety environments. Qualitative process modelling tools have been developed to allow representation of process complexities and informal process elements. Findings – Findings are presented on generic mechanisms for absorbing and mitigating the impact of variety on quotation processes. A generic quotation process model is presented comprising four key decisions centres: customization request initiation and information gathering on customer needs, classification of requests, resource control, and identification of information for reuse. Practical implications – The implications of the study for the automation of quotation processes in high variety and mass customization environments are discussed and it is speculated that different decision centres will dominate in different environments. Originality/value – The generic model developed by this research offers insight into the functioning of the core process elements of the quotation system. Reviewing an organisation’s structure and the information systems infrastructure supporting these decision centres should lead to the identification of potential system or reorganisation improvements.